2018
DOI: 10.4236/ojepi.2018.84019
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Its Treatment Quality in Benin (West Africa): Analysis of Data from the STEPS Survey 2015

Abstract: Aims: Diabetes is a major public health problem in low and middle-income countries. This study 1) estimated prevalence and factors associated with hyperglycemia in Benin, and 2) assessed the treatment quality of diabetes. Methodology: A cross-sectional research was conducted with two components. The First component has included 4954 subjects aged (18-69) randomly selected in Mono/Couffo and Donga regions. Data were collected according to WHO's STEPS approach. Capillary blood glucose was measured using the auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Fu et al with 4,506 subjects aged between 18 and 64 concluded that high household income was significantly associated with an increased risk of fasting hyperglycemia in rapidly changing rural Chinese communities (AOR = 1.93 (1.26-2.96); p = 0.002) [23]. On the contrary, Drame et al in Benin in 2015 did not find an association between hyperglycemia and socio-economic status (p = 0.62); which could be explained by the fact that their study area was extended to two administrative departments in Benin [24].…”
Section: Factors Associated With Fasting Hyperglycemiamentioning
confidence: 83%
“…Fu et al with 4,506 subjects aged between 18 and 64 concluded that high household income was significantly associated with an increased risk of fasting hyperglycemia in rapidly changing rural Chinese communities (AOR = 1.93 (1.26-2.96); p = 0.002) [23]. On the contrary, Drame et al in Benin in 2015 did not find an association between hyperglycemia and socio-economic status (p = 0.62); which could be explained by the fact that their study area was extended to two administrative departments in Benin [24].…”
Section: Factors Associated With Fasting Hyperglycemiamentioning
confidence: 83%
“…MSD program has been evaluated across a culturally diverse and underserved population in Mexico in a cluster-randomized controlled trial that shows the intervention significantly reduces the symptoms of diabetes among patients in the treatment arm after 3 and 12 months of intervention [ 26 ]. We argue that the MSD curriculum is feasible and practical to adapt in Benin, given the country’s low access to health education for people with diabetes [ 6 , 29 ]. Moreover, the community setting in Benin provides a unique opportunity to leverage family and community support for improving self-directed diabetes management.…”
Section: Methodsmentioning
confidence: 99%
“…The country faces unique challenges in fighting the disease, including inadequate funding, a lack of research and guidelines tailored to the population, and a shortage of medications [ 3 , 4 ]. Few T2D patients followed dietary guidelines (20%), exercised regularly (<40%), and adhered to prescribed treatments (10%) [ 5 , 6 ]. As a result, diabetes-related disabilities increased by 55.8% between 2007 and 2017.…”
Section: Introductionmentioning
confidence: 99%